2009
DOI: 10.1001/archophthalmol.2009.304
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Endophthalmitis After Intravitreal Drug Injection When Topical Antibiotics Are Not Required

Abstract: To report the incidence of endophthalmitis after intravitreal drug injection by means of a standardized procedure that does not require topical antibiotics, sterile gloves, or a sterile drape.Methods: Intravitreal injections of preservative-free triamcinolone acetonide or ranibizumab were administered in 2 prospective randomized clinical trials performed by the Diabetic Retinopathy Clinical Research Network. The standardized procedure for these trials requires the use of a topical combination product of povido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(40 citation statements)
references
References 19 publications
0
40
0
Order By: Relevance
“…Recent studies found that these are not an advantage in terms of reducing the rate of endophthalmitis [8,9]. However, since there is a rationale for their use (eliminating the bacterial conjunctival flora and reducing the pathogenicity of the surviving bacteria) [14,15], it is not surprising that according to the Green-Simms study [16], around 2/3 of the retinal specialists use them for IVT endophthalmitis prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies found that these are not an advantage in terms of reducing the rate of endophthalmitis [8,9]. However, since there is a rationale for their use (eliminating the bacterial conjunctival flora and reducing the pathogenicity of the surviving bacteria) [14,15], it is not surprising that according to the Green-Simms study [16], around 2/3 of the retinal specialists use them for IVT endophthalmitis prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…Halachmi-Eyal et al [6] concluded that endophthalmitis prophylaxis with preinjection of antibiotics does not reduce the endophthalmic rate, nor does it decrease the bacterial count any more than the use of PVI alone [7]. According to Bhavsar et al [8,9], the benefit of preinjection of topical antibiotics is not demonstrated. Besides, increased bacterial resistance to preinjection of antibiotics, particularly in the context of monthly repeated injections, has been described [2].…”
Section: Introductionmentioning
confidence: 99%
“…To minimize the risk of postinjection endophthalmitis, numerous guidelines, as evidenced by the studies reviewed, have been published [26,27,28]. Regarding prophylactic measures that can be taken during intravitreal injections, use of topical povidone-iodine and a sterile lid speculum could be considered to achieve a reduced rate of endophthalmitis [27].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding prophylactic measures that can be taken during intravitreal injections, use of topical povidone-iodine and a sterile lid speculum could be considered to achieve a reduced rate of endophthalmitis [27]. Use of povidone-iodine has been reported to be associated with a reduced number of colonies in culture and a confirmed reduction in the risk of postinjection infections [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation